Comparison of Antioxidant Activity of Crude Extract And Gel Preparation From Alstonia Scholaris L. Leaf Extract - Pratiwi, Puspa Dwi; Rizki, Nanda Putri; Elisma, Elisma; Maharini, Indri (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2023)
Alstonia scholaris L. contains several compounds, which has been proven to be potential as skin protection by formulating in gel preparation. The aims of this study were to obtained the antioxidant activity of crude extract from leaf part of Alstonia scholaris L. and gel preparation contain Alstonia scholaris L. leaf extract. Extract was prepared using destilled methanol by maceration method. The gel preparation was developed with extract (1% w/v) in carbomer base (1,67% w/v). The chemical compound was evaluated qualitatively used some reagent. The antioxidant assays performed by DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The result shown that methanolic extract of Alstonia scholaris leaf was found had flavonoids, tannins, phenols, alkaloids, saponins, and steroids compound. The methanolic crude extract and gel preparation had strong antioxidant activity with IC50 value was found to be 69,502 ppm and 86,832 ppm, respectively. From the result we conclude that the methanolic crude extract of Alstonia scholaris leaf sole has strong scavenging free radical activity even formulated in gel preparation but has decreased IC50 value.